Revisiting the effect of country size on taxation in developing countries - Thomas, Chrystol ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Investigates the effect of counry size has on tax revenues for developing countries. Discusses whether the findings of Codrington (1989) in the 1980s still hold in the twenty-first century.